2022
DOI: 10.1097/dbp.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Diagnosis and Treatment of Attention-Deficit/Hyperactivity Disorder in School-Age Children: Trends and Disparities During the COVID-19 Pandemic

Abstract: The aim of this study was to assess rates of primary care provider (PCP) diagnosis and treatment of school-age children with attention-deficit/hyperactivity disorder (ADHD) during the COVID-19 pandemic compared with prepandemic years and to investigate disparities in care. Method: We retrospectively analyzed electronic health records from all primary care visits (in-person and telehealth) of children aged 6 to 17 years seen between January 2016 and March 2021 in a community-based primary health care network (n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Consistent with these findings, we found that the number of patients visiting related to ADHD increased from 2.4 (per 1000 patients) in 2017 to 5.5 (per 1000 patients) in 2021 (Table 2), and similarly the number of patients being prescribed ADHD medication at least once annually increased from 12.9 (per 1000 patients) in 2017 to 21.9 (per 1000 patients) in 2021 (Table 3). A US retrospective cohort study involving children aged 6-17 years using electronic health records from primary care providers (mainly pediatricians) found that ADHD medication rates remained stable throughout the first year of the pandemic (March 15, 2020-March 15, 2021) [42]. We also found that ADHD medication prescribing patterns did not deviate significantly from prepandemic trends.…”
Section: Plos Onementioning
confidence: 52%
See 2 more Smart Citations
“…Consistent with these findings, we found that the number of patients visiting related to ADHD increased from 2.4 (per 1000 patients) in 2017 to 5.5 (per 1000 patients) in 2021 (Table 2), and similarly the number of patients being prescribed ADHD medication at least once annually increased from 12.9 (per 1000 patients) in 2017 to 21.9 (per 1000 patients) in 2021 (Table 3). A US retrospective cohort study involving children aged 6-17 years using electronic health records from primary care providers (mainly pediatricians) found that ADHD medication rates remained stable throughout the first year of the pandemic (March 15, 2020-March 15, 2021) [42]. We also found that ADHD medication prescribing patterns did not deviate significantly from prepandemic trends.…”
Section: Plos Onementioning
confidence: 52%
“…several studies have demonstrated that family physicians in North America are neither familiar with the diagnostic criteria for ADHD or use the criteria appropriately in their practices [16,25,26]. A US study found that ADHD management is not increasingly undertaken by recently trained pediatric primary care providers [42] and that pediatricians who were 10 years or more in practice were more likely to report regular ADHD care [44]. Family physician surveys in Ontario and British Columbia have indicated that most primary care physicians referred patients to a specialist for the diagnosis and management of ADHD [16,[45][46][47].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation